Relationship of Optimism Attitude with Academic Resilience Indeveloping Final Assignments of Nursing Science Students - Rully Annisa (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Various difficulties help students in preparing easy final assignments so that every student is required to have an attitude of optimism and high academic resilience. The purpose of this study was to determine the relationship between optimism and academic resilience in the preparation of the final assignments for Nursing Study Program students. Design: Non-experimental quantitative research Methdos: This research is non-experimental quantitative research with a cross-sectional approach. The total number of respondents was 44 students who were preparing their final project using the total sampling technique. Data collection used a questionnaire of optimism and The Academic Resilience Scale (ARS-30). Data analysis using Chi-Square Test. Results: The results of statistical tests showed 25 students (56.8%) had high optimism and 26 students (59.1%) had high academic resilience. In addition, this study resulted in a significance value of 0.009 (p-value <0.05). This means that there is a significant relationship between the attitude of optimism and academic resilience in the preparation of the final project of the Nursing Study Program students. Conclusions: Having an attitude of optimism and high academic resilience can make students always try to complete their final project, not fall into difficulties during the process of finalizing their final project.